Introduction of organic-organic eutectic PCM in mesoporous N-doped carbons for enhanced thermal conductivity and energy storage capacity. (1st February 2018) - Atinafu, Dimberu G.; Dong, Wenjun; Huang, Xiubing; Gao, Hongyi; Wang, Ge
Graphical abstract: The thermal conductivity of MA-SA was improved by 117.65% compared to that of the pristine value with high storage capacity using mesoporous N-doped porous carbon matrix as a supporting material. Highlights: Two simple strategies were employed for supporting materials synthesis. Mesoporous N-doped carbons/MA-SA shape stabilized PCMs were prepared. The loading of PCM in the composite PCMs could attain 88 wt% with high stability. The phase change enthalpy of the composite PCMs could achieve 164.33 kJ/kg. The composite attained enhanced thermal conductivity (up to 117.65%). Abstract: A systematic mesoporous N-doped carbons/myristic acid-stearic acid composite materials with improved thermal conductivity, energy storage density and shape stable performance were prepared by encapsulating myristic acid-stearic acids (MA-SA) eutectic mixture into porous carbon matrixes derived from two synthesis strategies. The effect of synthesis strategies and the N species present in porous carbons on the microstructure and thermal energy storage properties of composite phase change materials were studied by various characterization techniques. The results indicated that N-doped porous carbons derived from in situ (NPC) had maximum of up to 88 wt% PCM loading with a melting latent heat of 164.33 ± 0.29 kJ/kg, which was up to 45.69% higher than that of composite PCMs by post synthesis route (MGC/MA-SA). Factors, like pore characteristics, capillary force, surface tension and additional interaction with N species present in carbon matrix played vital roles for encapsulation of MA-SA to the pores of supporting materials. Notably, NPC/MA-SA composite materials exhibited excellent thermal conductivity, 117.65% higher than pristine PCM, while 74.59% for MGC/MA-SA. The content, homogeneous distribution and graphitic nature of N as well as the interconnected porous carbons improves the heat transfer pathways in the composite PCMs during phase change process. All the prepared samples were thermally and chemically compatible even after 100 times thermal cycling, confirming that the prepared composite materials were a promising candidates for thermal management system in a medium phase transition temperatures like domestic solar hot water supply and air-conditioning purposes.